Pengaruh Kompetensi Guru dan Motivasi Kerja terhadap Kinerja Guru SMK Swasta Wira Jaya Tanjung Morawa - Sadila, Laila; Tarigan, Nur M. Ridha; Nasution, Ismail (Universitas Islam Islam Sumatera Utara, 2023)
The purpose of this study is to know and analyze the effect of teacher competence and work motivation on teacher performance at Wira Jaya Tanjung Morawa Private Vocational School. The population and sample in this study were 30 people. Data collection techniques used interviews, questionnaires, documentation studies, and literature studies. The data analysis techniques used are data quality tests, classical assumption tests, multiple linear analysis and hypothesis tests. The results of this study show that partially (t-test) Teacher Competence has a positive and significant effect on the Performance of Wira Jaya Tanjung Morawa Private Vocational Teachers, and Work Motivation has a positive and significant effect on the Performance of Wira Jaya Tanjung Morawa Private Vocational Teachers. The results of simultaneous significant testing (F-test) of Teacher Competence and Work Motivation have a positive and significant effect on the Performance of Teachers of Private Vocational Schools Wira Jaya Tanjung Morawa. The suggestion of this research is as a reference material to improve competence and pay attention to providing work motivation for the performance of teachers of Wirajaya Tanjung Morawa Private Vocational SchoolTeacher Competence;Work Motivation;Teacher Performance